Menuju Desa Cerdas: Studi Kasus Pembangunan Desa Genteng di Sumedang, Jawa Barat, Indonesia: Towards Smart Village: A Case Study of Genteng Village Development in Sumedang, West Java, Indonesia - Sri Fatimah; Mochamad Gunardi Judawinata; Mochamad Nursiyam Barkah; Lucyana Trimo; Yosini Deliana (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This research aims to identify the prospects and challenges for implementing smart villages using a case study of Genteng Village in West Java, Indonesia, according to the sustainable development perspective and the enabler factors of socio-economic factors, village’s technology, and environmental aspects. This research uses a qualitative approach to assess the potencies and challenges from social, economic, environmental, and infrastructure perspectives. This research conducts a field survey with in-depth interviews and observation in Genteng Village, Sukasari Sub-district, Sumedang Regency, West Java Province to tap the information needed. Interviews with stakeholders were conducted with informants representing the rural stakeholders consisted of village official government, village local champion/leader, and farmer group representatives. Researcher involvement in nearly two years in regular visits and observations before this research has enriched and validated the information obtained. This research found prospective local social capital components and economic potencies to develop using the smart village framework. Environment and infrastructure are relatively still the challenges to be overcome towards the smart village. This research concludes that Genteng Village is on the right track, though early-stage to develop as a smart village. External factors, mainly information and communication technology, will be one of the main driving factors for optimism in implementing a smart village in Genteng Village.